Oral microbiota study of the patients after hospitalisation for COVID-19, considering selected dental indices and antibiotic therapy using the next generation sequencing method (NGS) - Barbara Brzychczy- Sroka; Katarzyna Talaga-Ćwiertnia; Agnieszka Sroka-Oleksiak; Artur Gurgul; Elżbieta Zarzecka-Francica; Wojciech Ostrowski; Janusz Kąkol; Joanna Zarzecka; Monika Brzychczy-Włoch (Journal of Oral Microbiology, 2023)
ABSTRACTBackground Poor oral hygiene and the increased incidence and severity of periodontitis may exacerbate SARS-CoV-2 infection. The aim was to evaluate the oral microbiota of 60 participants divided into groups: COVID-19 convalescents who received antibiotics during hospitalization (I), COVID-19 convalescents without antibiotic therapy (II) and healthy individuals (III).Materials and Methods Dental examination was conducted, and oral health status was evaluated using selected dental indexes. Clinical samples (saliva, dorsal swabs, supragingival and subgingival plaque) were collected and used for metagenomic library to the next-generation sequencing (NGS) preparation.Results Each of the clinical materials in particular groups of patients showed a statistically significant and quantitatively different bacterial composition. Patients from group I showed significantly worse oral health, reflected by higher average values of dental indexes and also a higher percentage of Veillonella, Tannerella, Capnocytophaga and Selenomonas genera in comparison to other groups. Additionally, a statistically significant decrease in the amount of Akkermansia type in both groups with COVID-19 was observed for all materials.Conclusions The primary factor affecting the composition of oral microbiota was not the SARS-CoV-2 infection itself, but the use of antibiotic therapy. The increased percentage of pro-inflammatory pathogens observed in COVID-19 patients underscores the importance of preventing periodontal disease and improving oral hygiene in the future.